Media Representation of Child Abuse and Its Policy Implications in Nigeria - Timothy Ekeledirichukwu Onyejelem; Muhammad Danjuma Abubakar; Omotola Ogunbola; Emmanuel Blessing Oyiza; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
Child abuse remains a significant social issue in Nigeria, with long-term consequences for victims and society. The media plays a crucial role in shaping public perception and policy responses to child abuse through its representation of cases, narratives, and framing of the issue. This study examines the media’s portrayal of child abuse in Nigeria, exploring the extent to which news coverage, documentaries, and other forms of media representation influence public awareness, government action, and policy formulation. It analyzes the dominant themes in media reports, including sensationalism, victim-blaming, and advocacy-driven narratives, while assessing the ethical and professional standards maintained by journalists in reporting such cases. Findings suggest that while the media has been instrumental in bringing child abuse cases to public attention, coverage is often inconsistent, and sometimes lacks depth, context, and follow-up reporting. Sensationalized stories may attract public outrage but do not always translate into sustained policy action or structural reforms. Additionally, cultural biases and societal stigma influence the framing of child abuse cases, sometimes shifting the blame onto victims or downplaying the role of systemic failures. This paper argues that effective media representation of child abuse should go beyond episodic reporting to include investigative journalism, human-centered storytelling, and advocacy for policy change. It highlights the need for training journalists on ethical reporting of child abuse and calls for stronger collaboration.